Mitos Manusia Super dalam Pieta dan The Death of Captain Marvel - Sasongko, Damar (Retorik: Jurnal Ilmu Humaniora, 2024)
The Pietà is a masterpiece in the world of sculpture by the renowned artist Michelangelo. Created more than five centuries ago (1497–1499), this work has often served as inspiration for artistic creations in later periods. In popular culture, the composition of the Pietà was once popularized and adapted for superhero comic book covers. Of the many comics, it is only in The Death of Captain Marvel (1982) by Jim Starlin that we find a strikingly similar likeness. This study examines the comparison between these two works and seeks to uncover the identity embedded within them. The Death of Captain Marvel exhibits intertextuality with the Pietà. In analyzing both, a shared identity emerges, encompassing name identity, origin identity, disguise identity, appearance identity (costume), strength identity, weakness identity, death identity, exposure identity, and resurrection identity.